2014
DOI: 10.1002/qua.24656
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and magnetic investigations of actinide‐based nanomagnets

Abstract: Magnetic exchange is an essential feature of transition-metal nanomagnets because it combines the relatively low spin-only moments of several ions into a "giant spin" ground state, which can make slow magnetic relaxation very favorable in an axially anisotropic environment. In contrast, most of the early research on lanthanidebased complexes focused on single-ion magnets, where the required large moment is generated by the unquenched orbital contribution (which is parallel to the spin in heavy rare earths). Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 32 publications
(46 reference statements)
0
26
0
Order By: Relevance
“…During recent decades, the magnetochemistry of actinide complexes has gained an important impetus, not only at the experimental level, but also at the theoretical one [1][2][3][4][5][6][7][8]. Indeed, since the first observation early in the 1990s of the antiferromagnetic (AF) coupling between uranium(V) centers in the para-imido [(MeC 5 H 4 ) 3 U] 2 (µ-1,4-N 2 C 6 H 4 ) complex by Rosen et al [9], this class of binuclear actinide systems has been arousing interest .…”
Section: Introductionmentioning
confidence: 99%
“…During recent decades, the magnetochemistry of actinide complexes has gained an important impetus, not only at the experimental level, but also at the theoretical one [1][2][3][4][5][6][7][8]. Indeed, since the first observation early in the 1990s of the antiferromagnetic (AF) coupling between uranium(V) centers in the para-imido [(MeC 5 H 4 ) 3 U] 2 (µ-1,4-N 2 C 6 H 4 ) complex by Rosen et al [9], this class of binuclear actinide systems has been arousing interest .…”
Section: Introductionmentioning
confidence: 99%
“…[1,5] However,i n2 003 seminalw ork by Ishikawa and coworkers revealed that bis-phthalocyanine lanthanide(III) compounds containing as inglep aramagnetic ion, Tb or Dy,e xhibited SMM behaviour as well. [10] Sincet hen, an increasing number of SMMs based on mononuclearl anthanide compounds [5,[11][12][13][14] and,m ore recently,m ononuclear actinide [5,[15][16][17][18] and transition-metal complexes [5,19] have been reported. These compounds are generally known as single-ionm agnets (SIMs).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, they can be considered to be better candidates to provide SIMs than lanthanides, as the J ground-state splitting caused by the ligand field is expected to be larger. [15,18] Although some examples have been reportedi n the last few years, SIMsb ased on actinides are still scarce and mainly restricted to U III species;a side from af ew distinct compounds, [16,17,26,27] most studies have focusedo np oly(pyrazolyl)borate uranium complexes. [28][29][30][31][32][33][34][35][36] These studies on wisely selected compounds could clearly evidence the effects of axial [27-29, 32-34, 36] and non-axial ligand environments, [16,17,27,31,35] magnetic dilution, [30] charge of the coligand, [31,35] different ligand donor strength in the same trigonal-prismatic [34] and tetrahedral [16] coordination geometries and also the first comparative studies with isostructurallanthanide complexes.…”
Section: Introductionmentioning
confidence: 99%
“…SMM behaviour has actually been observed in several monometallic U III [13] and U V [14] complexes and in heterometallic coordination compounds containing U V and either Mn II or Dy III cations [15][16][17]. The results obtained on these systems have been the subject of recent reviews [12,[18][19][20]. Here, we will critically summarize the attempts to obtain SMMs based on transuranic elements, mainly Np and Pu, focusing on the reasons for the limited success obtained so far and trying to indicate a possible direction for future research.…”
Section: Introductionmentioning
confidence: 91%
“…The results obtained on these systems have been the subject of recent reviews [12,[18][19][20]. Here, we will critically summarize the attempts to obtain SMMs based on transuranic elements, mainly Np and Pu, focusing on the reasons for the limited success obtained so far and trying to indicate a possible direction for future research.…”
Section: A Survey Of the Existing Transuranic Single Molecule Magnetsmentioning
confidence: 99%